Pengaruh ESG Disclosure, Struktur Modal, dan Kebijakan Dividen Terhadap Nilai Perusahaan dengan Profitabilitas Sebagai Variabel Moderasi - Frederika Novena Josevine; Susi Dwi Mulyani (As-Syirkah: Islamic Economic & Financial Journal, 2025)
This study was conducted to examine the influence of ESG disclosure, capital structure, and dividend policy on firm value with profitability as a moderating variable. The data used are panel data from 60 basic material sector companies listed on the IDX in 2022 to 2024, with 139 observations after outlier obtained using purposive sampling techniques and using Eviews 12 in data processing. The results of the study using a random effect model provide empirical evidence related to ESG disclosure has a positive effect on company value, capital structure has no effect on company value, dividend policy has no effect on company value, profitability is unable to strengthen the positive effect of ESG disclosure on company value, profitability is unable to strengthen the positive effect of capital structure on company value, and profitability is able to strengthen the positive effect of dividend policy on company value.